Answer:
-10
Step-by-step explanation:
-4 + -3 = -7
-7 + -2 = -9
-9 + -1 = -10
If you're looking for a fraction:
Think of it this way, the 9 is in the 10th place. The 6 is in front of the decimal. So, it's 69/10. The 10 takes the place of the 9, the "/" is the decimal moved to the right one space.
Or
If you're looking for a mixed number:
You basically split the above fraction "69/10" up into two separate pieces. So, it's
6 9/10.
Answer:
(a) (5, -3)
Step-by-step explanation:
The "substitution method" for solving a system of equations requires that you write an expression that can be substituted for a variable in one or more of the other equations in the system.
<h3>Expression to substitute</h3>
The given equations are ...
We notice the first equation gives an expression for y. This is exactly what we want to substitute for y in the second equation.
<h3>Substitution</h3>
When the expression (x-8) is substituted for y in the second equation, you get ...
2x +3(x -8) = 1
This simplifies to ...
5x -24 = 1
<h3>Solution</h3>
This 2-step equation can now be solved in the usual way:
5x = 25 . . . . . . add 24 to isolate the variable term
x = 25/5 = 5 . . . . . divide by the coefficient of x
Note that we now know what the correct answer choice is.
Using the expression for y, we find ...
y = x -8 = 5 -8 = -3
The solution is (x, y) = (5, -3).
__
The attached graph confirms this solution.
Answer: A
2x^2+2x-8 is the quotient when x+3 divides P(x)
=> P(x) = (2x² + 2x -8)(x + 3) = 2(x² + x - 4)(x + 3) = (x² + x - 4) (2x + 6)
=> the quotient when 2x+6 divides p(x) is x² + x - 4
Step-by-step explanation: